Slope topography effects on ground motion in the presence of deep soil layers - Tripe,R; Kontoe,S; Wong,TKC (Soil Dynamics and Earthquake Engineering, 2013)
An extensive investigation has been made into the interaction between topographic amplification and soil layer amplification of seismic ground motion. This interaction is suggested in the literature as a possible cause for the differences between topographic amplification magnitudes observed in field studies and those obtained from numerical analysis. To investigate this issue a numerical finite element (FE) parametric study was performed for a slope in a homogeneous linear elastic soil layer over rigid bedrock subjected to vertically propagating in-plane shear waves (Sv waves). Analyses were carried out using two types of artificial time history as input excitation, one mimicking the build-up and decay of shaking in the time histories of real earthquake events, and the other to investigate the steady-state response. The study identified topographic effects as seen in previous numerical studies such as modification of the free-field horizontal motion, generation of parasitic vertical motion, zones of alternating amplification and de-amplification on the ground surface, and dependence of topographic amplification on the frequency of the input motion. For the considered cases, topographic amplification and soil layer amplification effects were found to interact, suggesting that in order to accurately predict topographic effects, the two effects should not be always handled separately